Establishment of Mouse Primed Stem Cells by Combination of Activin and LIF Signaling - Wei, Mengyi; Chen, Yanglin; Zhao, Chaoyue; Zheng, Li; Wu, Baojiang; Chen, Chen; Li, Xihe; Bao, Siqin (Frontiers in Cell and Developmental Biology, 2021)
In mice, embryonic stem cells (ESCs) and epiblast stem cells (EpiSCs) are established from pre- and post-implantation embryos to represent the naïve and primed state, respectively. In here, we choose mouse leukemia inhibitory factor (LIF) which supporting ESCs self-renew and Activin A (Act A) which is the main factor in maintaining of EpiSCs to culture post-implantation epiblasts, and derive a primed stem cell lines, named ALSCs (medium was named AL medium). Like EpiSCs, ALSCs express key pluripotent genes Oct4, Sox2 and Nanog, and one of X chromosome was inactivation, as well as failed to contribute to chimaera in vivo. Notably, compared to EpiSCs, ALSCs efficiently reversed to ESCs (rESCs) by activating Wnt signaling. Moreover, we also discover culturing EpiSCs in AL medium for several passages and then Wnt signaling drived it to naïve pluripotency. Our results show ALSCs is another type primed state stem cell, it provides a simple method to study the pluripotent fate control and conversion from primed to naïve state.